Implication of Melanopsin and Trigeminal Neural Pathways in Blue Light Photosensitivity in vivo - Marek, Veronika; Reboussin, Elodie; Dégardin-Chicaud, Julie; Charbonnier, Angéline; Domínguez-López, Alfredo; Villette, Thierry; Denoyer, Alexandre; Baudouin, Christophe; Réaux-Le Goazigo, Annabelle; Mélik Parsadaniantz, Stéphane (Frontiers in Neuroscience, 2019)
Photophobia may arise from various causes and frequently accompanies numerous ocular diseases. In modern highly-illuminated world, complaints about greater photosensitivity to blue light increasingly appear. However, the pathophysiology of photophobia is still debated. In the present work, we investigated in vivo the role of various neural pathways potentially implicated in blue-light aversion. Moreover, we studied the light-induced neuroinflammatory processes on the ocular surface and in the trigeminal pathways. Adult male C57BL/6J mice were exposed either to blue (400-500 nm) or to yellow (530-710 nm) LED light (3 hours, 6 mW/cm2). Photosensitivity was measured as the time spent in dark or illuminated parts of the cage. Pharmacological treatments were applied: topical instillation of atropine, pilocarpine or oxybuprocaine; intravitreal injection of lidocaine, norepinephrine or “blocker” of the visual photoreceptor transmission; and intraperitoneal injection of a melanopsin antagonist. Clinical evaluations (ocular surface state, corneal mechanical sensitivity and tear quantity) were performed directly after exposure to light and after 3 days of recovery in standard light conditions. Mice were then sacrificed; trigeminal ganglia (TGs), brainstems and retinas were dissected out and conditioned for analyses. Mice demonstrated strong aversion to blue but not to yellow light. The only drug that significantly decreased the blue light aversion was the intraperitoneally injected melanopsin antagonist. After blue light exposure, dry-eye-related inflammatory signs were observed, notably after 3 days of recovery. We detected the increased immunoreactivity for cFOS and Iba1 in the sensory complex of trigeminal subnucleus, for ATF3 in the TG, and for GFAP, ATF3 and Iba1 in the retina. Moreover, retinal visual and non-visual light receptors distribution was altered. These data were corroborated by RT-qPCR. Thus, the wavelength-dependent light aversion was mainly mediated by melanopsin-containing cells, most likely in the retina. Other potential pathways of light reception were also discussed. The phototoxic message was transmitted to the trigeminal system, inducing both inflammation at the ocular surface and stress in the retina. Further investigations of retina-TG connections are needed.